Pengaruh Laju Pendinginan, Suhu, dan Lama Kristalisasi pada Profil Triasilgliserol dan Sifat Pelelehan Produk Fraksionasi Minyak Kelapa - . Mursalin; Purwiyatno Hariyadi; Eko Hari Purnomo; Nuri Andarwulan; Dedi Fardiaz (Jurnal Ilmu Pertanian Indonesia, 2013)
Dry fractionation will produce a fraction of olein and stearin with different composition of high melting and low melting as well the distribution of triacylglycerol (TAG) in the form of trisaturated (St3), disaturated (St2U) and monosaturated (StU2). This research aimed to study the effect of critical cooling rate and crystallization temperature on the composition and profile of TAG changes as well the melting properties of the fractionated coconut oil products. Coconut oilwas heated at 70°C then cooledat differentcooling rate to reach various crystalization temperatures. The oil was then stirred at 15rpm and allowed to crystallize at different period of time, and finally fractionated by vacuum filtration using Whatman #40 paper. Fractionation temperatures were the same as crystalization temperatures. The results showed that the critical cooling rate was proportional to the solid-like to liquid-like ratio, the content of St3 and SFC profile of olein fraction but inversely proportional to the content of St2U and StU2 TAG. Interval crystallization temperature between 21.30 and 21.73 °C produced the S/L ratio, the content of St3 TAG and SFC profiles of olein fractions lower and the content of St2U and StU2 TAG higher than the temperature interval below or above it. Coconut oil fractionation more effective in higher crystallization temperature or lower critical cooling rate. In these cooling treatments, St3 TAG which has high melting pointwould be concentrated at stearin fraction, while St2U and StU2 TAG and MCTwould be at olein fraction. Therefore, it will increase melting properties of stearin fraction and decrease olein fraction.